Outcome prediction in hospitalized COVID-19 patients: Comparison of the performance of five severity scores - Chung, Hsin-Pei; Tang, Yen-Hsiang; Chen, Chun-Yen; Chen, Chao-Hsien; Chang, Wen-Kuei; Kuo, Kuan-Chih; Chen, Yen-Ting; Wu, Jou-Chun; Lin, Chang-Yi; Wang, Chieh-Jen (Frontiers in Medicine, 2023)
Background: The aim of our study was to externally validate the predictive capability of five developed COVID-19-specific prognostic tools, including the COVID-19 SEIMC, Shang COVID severity score, COVID-IRS-NLR, inflammation-based score and VICE score. Methods: The medical records of all patients hospitalized for a laboratory-confirmed COVID-19 diagnosis between May 2021 and June 2021 were retrospectively analysed. Data were extracted within the first 24 hours of admission, and five different scores were calculated. The primary and secondary outcomes were 30-day mortality and mechanical ventilation, respectively. Results: A total of 285 patients were enrolled in our cohort. Sixty-five patients (22.8%) were intubated with ventilator support, and the 30-day mortality rate was 8.8%. The Shang COVID severity score had the highest numerical area under the receiver operator characteristic (AUC 0.836) curve to predict 30-day mortality, followed by the SEIMC score (AUC 0.807) and VICE score (AUC 0.804). For intubation, both the VICE and COVID-IRS-NLR scores had the highest AUC (AUC 0.82) compared to the inflammation-based score (AUC 0.69). The 30-day mortality increased steadily according to higher Shang COVID severity scores and SEIMC scores. The intubation rate exceeded 50% in the patients stratified by higher VICE scores and COVID-IRS-NLR score quintiles. Conclusions: The discriminative performances of the SEIMC score and Shang COVID severity score are good for predicting the 30-day mortality of hospitalized COVID-19 patients. The COVID-IRS-NLR and VICE showed good performance for predicting invasive mechanical ventilation.